What Does Liberal Arts Education Mean in Japan and South Korea? - Shimauchi, Sae; Yonezawa, Akiyoshi (International Higher Education, 2024)
<h3 id="international-liberal-arts-programs-in-japan-and-south-korea-face-the-challenge-of-integrating-western-inspired-education-into-national-identities-with-non-english-language-traditions-despite-their-global-orientation-national-contexts-still-play-a-crucial-role-in-shaping-the-endogenous-nature-of-the-dynamics-of-english-language-liberal-education-in-japan-and-south-korea-at-both-institutional-and-individual-levels" data-pm-slice="1 1 []">International liberal arts programs in Japan and South Korea face the challenge of integrating Western-inspired education into national identities with non-English language traditions. Despite their global orientation, national contexts still play a crucial role in shaping the endogenous nature of the dynamics of English-language liberal education in Japan and South Korea at both institutional and individual levels.